What is the New Future of Work for UX Research Practice? Assessing UX Research Practice During the COVID-19 Pandemic and Beyond - Snyder, Lauren; Hazen, R.; Hall, Amanda K. (International Conference on Human-Computer Interaction, 2023)
The User Experience (UX) Research profession was particularly impacted by the COVID-19 pandemic shift to remote work, as their work is largely dependent on engagements with customers, stakeholders, co-workers, and colleagues. The new future of work for UX research practice is still uncertain. Therefore, our study seeks to (1) address how COVID-19-associated remote work impacted UX research practice and (2) assess changes to UX research practice considerations, including methodologies, tools, and applications. We conducted a survey of UX research professionals with 52 open- and closed-ended questions to assess demographics, application and tool use, and UX research practice factors before and during the COVID-19 pandemic. A total of 220 UX research survey respondents world-wide responded to the survey. We found an increase in use of virtual applications and tools, virtual studies, and a mix of positive and negative COVID-19 impacts on UX research practice. Respondents reported changes to how they recruit participants, what study design methods they employ, how they analyze data, and how they share findings with stakeholders as likely to persist post pandemic. This study aimed to assess the impacts of remote work on UX research practice to support the new future of work initiatives and identify best practices.